2011
DOI: 10.5194/acp-11-2881-2011
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and air-sea exchange of mercury (Hg) in the Yellow Sea

Abstract: Abstract. The Yellow Sea, surrounded by East China and the Korea Peninsula, is a potentially important receptor for anthropogenic mercury (Hg) emissions from East Asia. However, there is little documentation about the distribution and cycle of Hg in this marine system. During the cruise covering the Yellow Sea in July 2010, gaseous elemental mercury (GEM or Hg(0)) in the atmosphere, total Hg (THg), reactive Hg (RHg) and dissolved gaseous mercury (DGM, largely Hg(0)) in the waters were measured aboard the R/V K… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
73
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 86 publications
(133 reference statements)
13
73
0
Order By: Relevance
“…Our concentrations were also higher than the mean concentrations (36.5 ± 14.9 pg L −1 ) of the northern SCS in the summer cruise but were very similar to those of stations near the Hainan Island (~40-80 pg L −1 , Fu et al 2010). Many field measurements also widely reported that the water Hg(0) concentrations in nearshore environments were generally higher than those in the open water (e.g., Mason et al 2001;Ci et al 2011d). The field observations and incubation experiments suggest that the special properties of nearshore environment, such as the enhanced THg levels, the estuarine mixing, and the high biological activity, can either promote the production of water Hg(0) and/or increase the Hg(0) input to the coastal water (Amyot et al 1997;Lanzillotta et al 2002;Rolfhus et al 2003;Covelli et al 2008;Fantozzi et al 2009;Schartup et al 2015;Ci et al 2016).…”
Section: Hg(0) In Watersupporting
confidence: 79%
See 1 more Smart Citation
“…Our concentrations were also higher than the mean concentrations (36.5 ± 14.9 pg L −1 ) of the northern SCS in the summer cruise but were very similar to those of stations near the Hainan Island (~40-80 pg L −1 , Fu et al 2010). Many field measurements also widely reported that the water Hg(0) concentrations in nearshore environments were generally higher than those in the open water (e.g., Mason et al 2001;Ci et al 2011d). The field observations and incubation experiments suggest that the special properties of nearshore environment, such as the enhanced THg levels, the estuarine mixing, and the high biological activity, can either promote the production of water Hg(0) and/or increase the Hg(0) input to the coastal water (Amyot et al 1997;Lanzillotta et al 2002;Rolfhus et al 2003;Covelli et al 2008;Fantozzi et al 2009;Schartup et al 2015;Ci et al 2016).…”
Section: Hg(0) In Watersupporting
confidence: 79%
“…A 47-mmdiameter Teflon pre-filter was placed in the inlet to remove the particle matter (including particulate Hg). This measurement was considered as that of atmospheric Hg(0) (Ci et al 2011d;Tseng et al 2012;Gustin et al 2015).…”
Section: Sampling Analysis and Measurementmentioning
confidence: 99%
“…These GEM concentrations are statistically lower (t-test, P < 0.05) than our previous summer cruise (July 2010) covering the similar sea region (2.61 ± 0.50 ng m À3 , Ci et al, 2011d). The GEM data of the three cruises suggest the high concentrations during the summer cruise and low concentrations during the spring cruise and fall cruise.…”
Section: Gem In Airmentioning
confidence: 75%
“…However, the accuracy of the modeling result is difficult to evaluate because of limited field data, especially those related to marine system (Jaffe and Strode, 2008;Ci et al, 2012). At present, most atmospheric Hg measurements focused on the coastal region of East Asia (e.g., Wang et al, 2007;Ci et al, 2011b;Nguyen et al, 2010;Xiu et al, 2009), but the investigations focusing on the open ocean are limited (Friedli et al, 2004;Ci et al, 2011d;Nguyen et al, 2011;Fu et al, 2010;Tseng et al, 2012;Sheu et al, 2013). The lack of Hg knowledge in the open ocean of East Asia has become a critical barrier to the current understanding of the regional and global Hg cycles (Jaffe and Strode, 2008;Ci et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation